Posterior division of ipsilateral C7 transfer to C5 for shoulder abduction limitation - Huang, Xinying; You, Zongqi; Xiang, Yaoxian; Dai, Junxi; Jiang, Junjian (Frontiers in Neurology, 2023)
Background Reparation of C5 by proximal selective ipsilateral C7 transfer has been reported for the treatment of neurogenic shoulder abduction limitation as an alternative to the reparation of the suprascapular nerve (SSN) and the axillary nerve (AXN) by distal nerve transfers. However, there is a lack of evidence to support either strategy leading to better outcomes based on long-term follow-up. Objective The purpose of the study was to investigate the safety and long-term outcomes of the posterior division of ipsilateral C7 (PDIC7) transfer to C5 in treating neurogenic shoulder abduction limitation. Methods A total of 27 cases with limited shoulder abduction caused by C5 injury (24 cases of trauma, 2 cases of neuritis, and 1 case of iatrogenic injury) underwent PDIC7 transfer to the C5 root. A total of 12 cases (11 cases of trauma and 1 case of neuritis) of C5 injury underwent spinal accessory nerve (SAN) transfer to SSN plus the triceps muscular branch of the radial nerve (TMBRN) transfer to AXN. The patients were followed up for at least 12 months for muscle strength and shoulder abduction range of motion (ROM). Results In cases that underwent PDIC7 transfer, the average shoulder abduction was 105.9° at the 12-month follow-up. In total, 26 of 27 patients recovered at least M3 (13 reached M4) (Medical Research Council Grading) of the deltoid. In cases that underwent SAN transfer to SSN plus TMBRN to AXN, the average shoulder abduction was 84.6° at the 12-month follow-up. In total, 11 of 12 patients recovered at least M3 (4 reached M4) of the deltoid. Conclusion Posterior division of ipsilateral C7 transfer is a one-stage, safe, and effective surgical procedure for patients with neurogenic shoulder abduction limitation.